Improving The Restaurant Product Sale: A Case Study at a Hotel in Surabaya - Anshori, Mohamad Yusak (International Research Journal of Business Studies, 2012)
Increasing a product sale is very important especially for the hotel with its products and services. The objective of this study is to examine the effect of Nasi Goreng Jancuk (Nasgorcuk) marketing mix on its selling improvement. The increasing of Surabaya Plaza Hotel’s Nasgorcuk lovers is based on strategic product marketing efforts conforming very fast communication development in which youths involvement very dominantly affects the success of a brand image. The fundamental marketing strategies consist of promotion, price, location; persons, physical evidence and process are inherent attributes of the success of Surabaya Plaza Hotel’s Nasgorcuk. The findings show that price, location, and physical evidence are the most influential attributes of the increased sale of Nasgorcuk.